Chapter 7: Ethnographic approaches in terrorism studies and research - Filippidou, Anastasia (Edward Elgar Publishing, 2023)
Ethnographic approaches have played a significant part in terrorism research. This chapter examines the strengths and challenges of the ethnographic approach. The chapter draws on the author’s fieldwork experiences investigating violent ethnonational conflicts, predominantly from the cases of Spain/Basque country, France/Corsica, UK/Ireland, and Israel/Palestine. It is argued that ethnographic approaches can provide a very useful umbrella research method for terrorism studies, with the capacity to deal with a range of critical themes. A key recommendation is the importance and utility of a pragmatic empathetic ethnographic approach in researching terrorism and political violence.
Keywords: Ethnography; Terrorism research; Violent ethnonational conflicts